Mid-ocean ridge (MOR) and suprasubduction zone (SSZ) geological events in the Yarlung Zangbo suture zone: Evidence from the mineral record of mantle peridotites. (1st October 2015) - Guo, Guolin; Yang, Jingsui; Liu, Xiaodong; Xu, Xiangzhen; Liu, Zhao; Ba, Dengzhu
Highlights: In-situ mineral composition are sensitive indicators of the evolution of periotites. Olivine, spinel and pyroxene overlap the fields of abyssal and SSZ peridotites. Mineral textures and compositions documented the MOR- and SSZ-geological events. Abstract: The Purang ophiolite in the westernmost Yarlung-Zangbo suture zone of southern Tibet shows a two-stage evolution, on the basis of its mineralogy and geochemistry, having formed originally at a mid-ocean spreading ridge and later been modified in a suprasubduction zone (SSZ) environment. Olivine from the Purang peridotites is highly magnesian (Fo90–92 ) with NiO contents of 0.32–0.48 wt%, consistent with formation in a fore-arc environment. Magnesiochromite in the mantle peridotites has a large range in Mg# [100Mg/(Mg + Fe)] (43.6–67.7) and Cr# [100Cr/(Cr + Al)] (22.3–67.8), reflecting different degrees of partial melting and melt–rock reaction. The Cr#s increase and the Mg#s decrease systematically from lherzolite to harzburgite to dunite. Magnesiochromites in the harzburgites and lherzolites are analogous to those from abyssal peridotites and MORB-like ophiolites, whereas those in clinopyroxenites and cumulate orthopyroxenites are typical of SSZ ophiolites, suggesting refertilization of the peridotites by metasomatic fluids/melts. This interpretation is supported by the "U-shaped", chondrite-normalized rare earth element (REE) patterns of Purang mantle peridotites. Plots of TiO2 and Al2 O3 vs. Mg# show that both the orthopyroxenes and clinopyroxenes overlap the fields of abyssal and SSZ peridotites indicating a transition from a MOR to a SSZ setting for the Purang peridotites.